Modeling biomedical experimental processes with OBI - Brinkman Ryan R; Courtot Mélanie; Derom Dirk; Fostel Jennifer M; He Yongqun; Lord Phillip; Malone James; Parkinson Helen; Peters Bjoern; Rocca-Serra Philippe; Ruttenberg Alan; Sansone Susanna-Assunta; et al. (Journal of Biomedical Semantics, 2010)
Abstract Background Experimental descriptions are typically stored as free text without using standardized terminology, creating challenges in comparison, reproduction and analysis. These difficulties impose limitations on data exchange and information retrieval. Results The Ontology for Biomedical Investigations (OBI), developed as a global, cross-community effort, provides a resource that represents biomedical investigations in an explicit and integrative framework. Here we detail three real-world applications of OBI, provide detailed modeling information and explain how to use OBI. Conclusion We demonstrate how OBI can be applied to different biomedical investigations to both facilitate interpretation of the experimental process and increase the computational processing and integration within the Semantic Web. The logical definitions of the entities involved allow computers to unambiguously understand and integrate different biological experimental processes and their relevant components. Availability OBI is available at http://purl.obolibrary.org/obo/obi/2009-11-02/obi.owl